Edukasi Gaya Hidup Sehat untuk Meningkatkan Kebugaran Akseptor KB Hormonal - Luluk Yuliati; Irfana Tri Wijayanti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
The use of hormonal contraception is one of the family planning methods most commonly chosen by women of childbearing age due to its effectiveness and ease of use. However, acceptors' understanding of healthy lifestyles that support physical fitness is still limited, so that various health complaints are often attributed solely to the contraception used. This community service activity aims to increase the knowledge of hormonal contraceptive users about healthy lifestyles as an effort to maintain fitness. The target of this activity is 20 hormonal contraceptive users in the partner area. The implementation method uses a participatory educational approach through interactive lectures, discussions, question and answer sessions, as well as simple practices of light physical activities and relaxation techniques. Evaluation is carried out using pre-test and post-test knowledge. The results showed an increase in participants' knowledge scores, from a range of 50–70 before education to 75–95 after the activity. Participants also showed an increase in understanding of the importance of a balanced diet, regular physical activity, stress management, and good sleeping patterns. The discussion relates these findings to health education theory, social learning, and andragogy, which emphasize the importance of active involvement in the adult learning process. This activity not only increases knowledge, but also encourages a change in attitude towards the importance of healthy living. Community-based healthy lifestyle education has the potential to improve the fitness of hormonal contraceptive users and have a positive impact on their families and surrounding environment. Similar programs are recommended to be carried out on an ongoing basis to reinforce long-term health behavior change.